The road out of debt : bankruptcy and other solutions to your financial problems - Feeney, Joan N.; Connolly, Thoedore W. (John Wiley & sons, 2010)
"A practical guide to getting out of debt and understanding the option of personal bankruptcyThe current credit and financial crises have prompted Joan Feeney, a preeminent Massachusetts Bankruptcy Judge, and Theodore Connolly, a Finance and Bankruptcy Attorney, to write a book that will help people handle their financial troubles. The Road Out of Debt seeks to assist those considering bankruptcy by demystifying the bankruptcy process and explaining what you can expect to gain (or lose) from it.With the insights of both a bankruptcy judge and a bankruptcy lawyer, you?ll be able to determine when it?s best to avoid bankruptcy, when you should seek bankruptcy protection, and, most importantly, how best to work through the bankruptcy process, if you so choose. With millions of Americans personally facing dire financial situations, job losses, home foreclosures, and other major financial challenges, no book could be more timely.An exceptional resource for anyone contemplating bankruptcy or otherwise trying to figure out how to handle their debtPuts the bankruptcy process in perspective and reveals specific steps to followDiscusses how to decide whether or not bankruptcy is the right path for youWritten by a well-respected bankruptcy judge and bankruptcy attorneyAs more people find themselves entering financial difficulties, an increasing number of them will need information to help them through these problems. The Road Out of Debt provides you with the serious solutions needed to overcome a personal financial crisis"-- Provided by publisher